Kebijakan Pengadaan dan Customisasi CN-235 MPA (Maritime Patrol Aircraft) dalam Rangka Pengawasan wilayah ZEE dan ALKI di Indonesia - Endro Tri Susdarwono (Dinamika Bahari, 2021)
The potential of Indonesia's maritime natural resources is one of the targets desired by several countries from the international world to strengthen their economy. In addition to the natural resources it contains, Indonesia also has a strategic value for the world economy. The potential of Indonesia's maritime natural wealth demands the availability of qualified maritime security that can guard against acts of lawlessness, environmental pollution, exploitation of natural resources, navigational hazards, and territorial violations. Maritime Patrol Aircraft (MPA) is a tool that is considered appropriate to maintain security in the maritime environment. The purpose of this study is to describe the procurement and customization of N-235 MPA in the context of monitoring and securing the EEZ and ALKI areas in Indonesia. This study uses a descriptive approach. This type of research is descriptive qualitative. The result of the research is that the Maritime Patrol Aircraft with specifications in the form of a small aircraft (medium range aircraft) that is fuel efficient and does not require a long runway, to land so that it can land on an emergency runway (airship). This aircraft is suitable for reaching all sea border areas that are difficult to access in detecting suspicious activity, especially in the EEZ and ALKI areas. This aircraft has a radar with a wide range of monitors, surveillance cameras, and sophisticated weapons systems.